Crescimento, hematologia e parâmetros oxidativos de jundiás (Rhamdia quelen) alimentados com dietas contendo vitamina A - Battisti, Eduardo Kelm (2016)
Vitamin A is a fat soluble compound occurring in three chemical forms in animal tissues: alcohol (retinol), aldehyde (retinal) and acid (retinoic acid). It is an essential nutrient for fish, required in small quantities, important for the health, growth and reproduction. In this study, the objective was to determine the nutritional requirement and the response in growth, hematological disorders and oxidative parameters of juvenile catfish (Rhamdia quelen) fed diets with vitamin A. We conducted an experiment lasting 70 days, with 500 silver catfish (initial weight = 23.00 ± 4.27 g), distributed in 20 tanks (25 fish per tank), with four replications. The semi-purified diets were formulated to meet the protein and energy requirements of the species (37% CP and 3.400 kcal/kg DE). Five vitamin A levels were tested: 0; 1500; 3000; 4500; 6000 IU kg-1. Fish were fed three times a day (8, 12 and 18 hours), at 3% PV. Three sampling was performed at the beginning, the middle and the end of the experiment. The following parameters were measured: average weight (g), total length and standard length (cm). Fish used to collect tissue samples were killed by benzocaine overdose (dose: 35 mg L-). Liver, gills and muscle samples were collected to determine oxidative stress parameters (tissue protein, TBARS non-protein thiols, catalase, superoxide dismutase, glutathione-S-transferase). Hematological analyzes of fish were made by analyzing the total number of red blood cells, hematocrit, hemoglobin, mean corpuscular volume, mean corpuscular hemoglobin and mean corpuscular hemoglobin concentration. Analysis of body composition (crude protein, fat, dry matter and mineral matter) of silver catfish to whole fish and fillet samples were also carried out. It has been found that providing diets with levels greater than 3500 IU of vitamin A kg- is ideal for better growth, animals increased proportionally to the increase of vitamin A in the diet. There were no effects on hematological and biochemical parameters of plasma. Considering the fillet quality parameters the level of 4500 IU kg- of vitamin A in the diet showed better results, there were a higher amount of protein and less fat in the fillet. To oxidative protection the level of 4500 IU kg- of vitamin A in the diet showed better results too, was observed lower activity of enzymes that act as an antioxidant, proving that retinoids and carotenoids act by donating electrons to reactive oxygen species, saving the enzymatic protection.